World civilizations : - Meacham, Standish.; Lerner, Robert E.; Ralph, Philip Lee. (W. W. Norton, 1997)
This book is divided into three parts: The French and industrial revolutions and their consequences; The West at the world's center; and The emergence of world civilization.